Judgement at Tokyo : World War II on trial and the making of modern Asia - Bass, Gary J., (Jonathan) 1969- (New York : Alfred A. Knopf, 2023)
"In the weeks after Japan finally surrendered to the Allies, the world turned to the question of how to move on from years of carnage and destruction. For Harry Truman, Douglas MacArthur, and their fellow victors, the questions of justice seemed clear: Japan's leaders needed to be tried and punished for the surprise attack at Pearl Harbor; shocking atrocities against citizens in China, the Philippines, Korea, and elsewhere; rampant abuses of POWs. For the Allied Forces, the trial was an opportunity to achieve justice against the defendants, but also to create a legal framework for the prosecution of war crimes and to prohibit the use of aggressive war, and to create the kind of liberal international order that would prevail in Europe. For the Japanese leaders facing trial, it was their chance to argue that their war had been waged to liberate Asia from Western imperialism. For more than two years, lawyers for both sides presented their cases before a panel of judges from China, India, the Philippines, and Australia, as well as the US and Europe. The testimony ran from horrific accounts of brutality and the secret plans to attack Pearl Harbor to the Japanese military's threats to destabilize the government if it sued for peace. Yet rather than clarity and unanimity, the trial brought division and complexity; these tensions and contradictions could also be seen playing out across Asia as the trial unfolded, from China's descent into civil war to India's independence and partition to Japan's first successful democratic elections and the rewriting of a new, liberal constitution"--
Nuremberg to Tokyo -- Unconditional surrender -- "Prompt and utter destruction" -- Atomic fire -- Supreme commander -- Apprehensions -- "When the emperor violates the law" -- The god that failed -- The Imperial Hotel -- The anatomy of the Tokyo Trial -- "Asia for the asiatics" -- The first conquest -- The rape of Nanjing -- Remember Pearl Harbor -- The narrow road to the deep north -- Eleven angry men -- The defense rises -- A very British coup -- Denial at Nanjing -- Self-defense at Pearl Harbor -- The emperor waltz -- "The great sorrow of my life" -- Tojo takes the stand -- Mr. X -- Days of judgment -- "Blowing up a ton of dynamite" -- Judgment at Tokyo -- Dissensus -- "I am wholly dissenting" -- Equal justice under law -- One minute after midnight -- A silent prayer -- The inescapable purge of comrade Mei -- Epilogue : martyrs of Showa.
Includes bibliographical references (pages 695-850) and index.
Keywords: International Military Tribunal for the Far East; Tokyo Trial, Tokyo, Japan, 1946-1948.; War crime trials -- Japan -- History -- 20th century; World War, 1939-1945 -- Campaigns -- Pacific Area -- Atrocities